Dynamics of Mono- and Dual-Species Biofilm Formation and Interactions Between Paracoccidioides brasiliensis and Candida albicans - Oliveira, Lariane Teodoro; Medina-Alarcón, Kaila Petronila; Singulani, Junya de Lacorte; Fregonezi, Nathália Ferreira; Pires, Regina Helena; Arthur, Rodrigo Alex; Fusco-Almeida, Ana Marisa; Mendes Giannini, Maria José Soares (Frontiers in Microbiology, 2020)
Oral cavity is a highly diverse microbial environment in which micro-organisms interact to each other growing as biofilms on biotic and on abiotic surfaces. Understanding the interaction among oral microbiota counterparts is pivotal for clarifying the pathogenesis of oral diseases. Candida spp. is one of the most abundant fungi of the oral mycobiome being able to cause severe soft tissue lesions under certain conditions. Paracoccidioides spp., the causative agent of paracoccidioidomycosis, may also colonize the oral cavity leading to the development of soft tissue damage. The hypothesis was raised that both fungi can interact with each other, increasing the growth of the biofilm and its virulence, which in turn can lead to a more aggressive infectivity. Therefore, this study aimed to evaluate the dynamics of mono- and dual-species biofilm growth of Paracoccidioides brasiliensis and Candida albicans and their infectivity using Galleria mellonella model. Biomass and fungi metabolic activity were determined by the crystal violet method and by the tetrazolium salt reduction test (XTT), respectively, and the colony-forming unit (CFU) was obtained by plating. Biofilm structure was characterized by both scanning electronic- and confocal laser scanning- microscopy techniques. Survival analysis of G. mellonella was evaluated to assess infectivity. Our results showed that dual-species biofilm with P. brasiliensis + C. albicans presented higher biomass, higher metabolic activity and CFU than their mono-species biofilms. Furthermore, G. mellonella larvae infected with P. brasiliensis + C. albicans presented a decrease in the survival rate compared to those infected with P. brasiliensis or C. albicans, mainly in the form of biofilm. These data indicate an apparent synergistic interaction for one or both fungi when co-infected using in vitro and in vivo analysis. These data contribute to expand the knowledge associated with dynamics of fungal biofilm growth that can potentially lead to the discovery of new therapeutic strategies for these infections.